MANAJEMEN “SEKOLAH KAOETAMAAN ISTRI” RADEN DEWI SARTIKA DALAM MENINGKATKAN KETERAMPILAN KAUM WANITA SUNDA - Ibrahim, Tatang (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
AbstractThis study aims to reveal information about his struggle in improving the quality of education of Sundanese women, more specifically in their skills. The vision carried by Raden Dewi Sartika is ”Mun jadi awéwé kudu miboga keterampilan, kudu sagala bisa, ambéh bisa hirup”,, the meaning is woman have everything possible in order to live. It means that a woman should be smart (cognitive), polite (affective) to her husband and anyone, and have the skills (psychomotor).The success played by Raden Dewi Sartika in managing his institution, certainly not without reason. He applied the management education in accordance with the conditions at that time. A good institution can not be separated from the implementation of good management as well. The study of management applied by Raden Dewi Sartika is the subject of management's perspective.This research uses qualitative approach with descriptive analytic method. The method used is observation and documentation. Data analysis phase is data reduction, as well as conclusion and verification (Conclusion and verification).The management of Raden Dewi Sartika in managing hereducation has followed the management concepts by J. David Hanger, this can be seen directly in the implementation of the environment, planning, management, supervision and evaluation. In this connection the authors are interested to conduct research on the management carried out by Raden Dewi Sartika in managing his education named Sekolah Kautamaan Istri.